Cell-Free Biomimetic Mineralization Strategies to Regenerate the Enamel Microstructure - Yu Yuan Zhang (MDPI AG, 2021)
The distinct architecture of native enamel gives it its exquisite appearance and excellent intrinsic-extrinsic fracture toughening properties. However, damage to the enamel is irreversible. At present, the clinical treatment for enamel lesion is an invasive method; besides, its limitations, caused by the chemical and physical difference between restorative materials and dental hard tissue, makes the restorative effects far from ideal. With more investigations on the mechanism of amelogenesis, biomimetic mineralization techniques for enamel regeneration have been well developed, which hold great promise as a non-invasive strategy for enamel restoration. This review disclosed the chemical and physical mechanism of amelogenesis; meanwhile, it overviewed and summarized studies involving the regeneration of enamel microstructure in cell-free biomineralization approaches, which could bring new prospects for resolving the challenges in enamel regeneration.